2005
DOI: 10.1007/s11240-004-4783-1
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium rhizogenes is a useful transporter for introducing T-DNA of the binary plasmid into the chrysanthemum, Dendranthema grandiflorum Kitamura, genome

Abstract: Agrobacterium rhizogenes was used for efficient transformation of chrysanthemum. Two types of Agrobacterium, A. rhizogenes (A-13) and A. tumefaciens (LBA4404), which harbor pIG121-Hm, were employed for infection. In the A. rhizogenes-infected explants, hairy roots were not observed on any tested medium or culture condition. When explants were cultured on shoot induction medium, calli were formed at the cutting edge within 4-6 weeks of culture, and shoot primordia were observed on the callus surface after 2 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…In other studies, aberrant phenotype of tobacco plants (Dehio et al 1993), delayed senescence, shortened style (van Altvorst et al 1992), and reduced fertility (Sun et al 1991) have been reported in rolA transformants, while Osteosperum ecklonis rolA transformants produced profuse rooting with shorter branching and slightly earlier flowering (Giovannini et al 1999). Similarly, rolC transformants have shown dwarf phenotype with reduced apical dominance, early inflorescence, variation in leaf size and leaf number, and increased rooting ability in many plant species, including Rosa hybrida, Petunia hybrida, Pelargonium, Atropa belladonna, Osteospermum ecklonis, Malus micromalus, Chrysanthemum morifolium, and Nicotiana tabacum (for a review, see Casanova et al 2005;Tsuro et al 2005).…”
Section: Resultsmentioning
confidence: 98%
“…In other studies, aberrant phenotype of tobacco plants (Dehio et al 1993), delayed senescence, shortened style (van Altvorst et al 1992), and reduced fertility (Sun et al 1991) have been reported in rolA transformants, while Osteosperum ecklonis rolA transformants produced profuse rooting with shorter branching and slightly earlier flowering (Giovannini et al 1999). Similarly, rolC transformants have shown dwarf phenotype with reduced apical dominance, early inflorescence, variation in leaf size and leaf number, and increased rooting ability in many plant species, including Rosa hybrida, Petunia hybrida, Pelargonium, Atropa belladonna, Osteospermum ecklonis, Malus micromalus, Chrysanthemum morifolium, and Nicotiana tabacum (for a review, see Casanova et al 2005;Tsuro et al 2005).…”
Section: Resultsmentioning
confidence: 98%
“…Transformation was performed according to the method of Tsuro et al (2005). Putative transformants were screened for the presence of rolC genes by PCR analysis.…”
Section: Plant Transformationmentioning
confidence: 99%
“…Why one plant without rolC regenerated from hairy roots is unclear. Tsuro et al (2005) found that wild-type A. rhizogenes (with pIG121-Hm) transported T-DNA of binary plasmid more efficiently than Ri-T-DNA alone in chrysanthemum. From our results and the above report, a transformant without rolC might have been regenerated from an adventitious root that included only T-DNA of the binary plasmid, not from a hairy root.…”
Section: Hairy Root Formation and Regenerationmentioning
confidence: 93%
“…It has been used to introduce binary plasmid T-DNA into plant genomes, e.g., petunia and melon (Kiyokawa et al, 1992;Toyoda et al, 1991). Tsuro et al (2005) suggested that…”
Section: Introductionmentioning
confidence: 99%